Patterns of human behaviour in public urban green spaces: On the influence of users' profiles, surrounding environment, and space design - Vidal, Diogo Guedes (2022)
Public urban green spaces (PUGS) play a vital role in the dense urban fabric as places of Nature-Society contact and socialization. Despite some advances in the field, the relationship between the PUGS surroundings and their users' behaviours remains unclear. This study examined the patterns of human behaviour in four PUGS of the city of Porto, on the north Portuguese coast, where the behavioural mapping method was applied. Observational data regarding 979 PUGS users' socio-demographics and behaviours were recorded on a base map and a grid between August and November 2020. The use patterns during different times of the day were disaggregated across behaviours and users' profiles, and their relationship with the surroundings and design elements was assessed with ANOVA, Chi-Square test, and Pearson correlation. The findings presented may pave the way for future studies and inform the urban planning and design of the effectiveness of new interventions, namely providing more accurate aligning between the greenspace design language with users' needs. Furthermore, this study highlights the importance of considering the sociodemographic background of PUGS users and the surroundings to guide designers and planners.